Case Report: Viral Conjunctivitis in A 35-Year-Old Male With Upper Respiratory Infection History - Anindita Putri Noorma Rahayu; Nasrudin Nasrudin; Saskia Nassa Mokoginta (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
The conjunctiva is a protective ocular tissue essential for lubrication and immune defense. While typically self-limiting, conjunctivitis can arise from various etiologies, requiring accurate diagnosis to prevent complications. Case Report: A 35-year-old male presented with a four-day history of redness in the left eye, accompanied by itching, epiphora, watery discharge, and photophobia. Notably, the symptoms followed an Upper Respiratory Tract Infection (URTI) and frequent outdoor dust exposure, which likely compromised the ocular surface integrity. Examination showed minimal upper eyelid edema, conjunctival injection, and scleral hyperemia, with preserved visual acuity. The patient was managed with supportive therapy using artificial tears and strict hygiene education. The prognosis was favorable. Viral conjuctivitis is frequently associated with systemic viral prodromes and environmental triggers like dust. This case underscores the efficacy of supportive management and patient education in achieving optimal clinical outcomes for uncomplicated viral conjunctivitis.